2021
DOI: 10.1113/ep089501
|View full text |Cite
|
Sign up to set email alerts
|

Swimming exercise decreases depression‐like behaviour and inflammatory cytokines in a mouse model of type 2 diabetes

Abstract: Clinical and experimental studies have shown that type 2 diabetes is associated with depression-related disorders. Inflammation has been identified as a common mechanism in both type 2 diabetes and depression. Several studies have suggested that swimming exercise might be able to reduce depression-related symptoms. The present study aimed to explore whether swimming exercise can decrease depressionlike behaviour in type 2 diabetic mice. To induce type 2 diabetes, male C57BL6 mice were treated with a high-fat d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…This finding in the FST agrees with other studies using longer exercise interventions (1.5-11 months) in adult male mice (Fuss et al, 2010;Morgan et al, 2018), but not with studies using 3-4-week interventions which demonstrated a decrease in immobility following exercise (Duman et al, 2008;Cunha et al, 2013). Our finding in the FUST that there were no effects of exercise on reward-seeking behaviour has similarly been reported by others in adult male rodents using the sucrose preference test (Sigwalt et al, 2011;Gilak-Dalasm et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…This finding in the FST agrees with other studies using longer exercise interventions (1.5-11 months) in adult male mice (Fuss et al, 2010;Morgan et al, 2018), but not with studies using 3-4-week interventions which demonstrated a decrease in immobility following exercise (Duman et al, 2008;Cunha et al, 2013). Our finding in the FUST that there were no effects of exercise on reward-seeking behaviour has similarly been reported by others in adult male rodents using the sucrose preference test (Sigwalt et al, 2011;Gilak-Dalasm et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, there is a reduction in epilepsy co-morbidities. In addition, studies have shown that moderate physical exercise could reduce the levels of IL-1β and TNF-α in the hippocampus or serum ( 86 , 87 ) in interventions for brain disorders, although the effect on IL-6 is subject to specific discussion. To illustrate, physical exercise can reduce IL-6 levels in the hippocampus and cerebellum ( 88 , 89 ).…”
Section: Discussionmentioning
confidence: 99%